Dose-Dependent Effects of Aloin on the Intestinal Bacterial Community Structure, Short Chain Fatty Acids Metabolism and Intestinal Epithelial Cell Permeability - Gokulan, Kuppan; Kolluru, Pranav; Cerniglia, Carl E.; Khare, Sangeeta (Frontiers in Microbiology, 2019)
Aloe leaf or purified aloin products possess numerous therapeutic and pharmaceutical properties. It is widely used as ingredients in a variety of food, cosmetic and pharmaceutical products. Animal studies have shown that consumption of aloe or purified aloin cause intestinal goblet cell hyperplasia, and malignancy. Here, we tested antibacterial effects of aloin, against intestinal commensal microbiota. Minimum inhibitory concentration of aloin for several human commensal bacterial species (Gram+ve and Gram-ve) ranged from 1 to 4 mg/ml. Metabolism studies indicated that Enterococcus faecium was capable of degrading aloin into aloe-emodin at a slower-rate compared to Eubacterium spp. As a proof of concept, we incubated 3% rat fecal-slurry (an in vitro model to simulate human colon content) with 0.5, 1, and 2 mg/ml of aloin to test antimicrobial properties. Low aloin concentrations showed minor perturbations to intestinal bacteria, whereas high concentration increased Lactobacillus spp. counts. Aloin also decreased butyrate-production in fecal microbiota in a dose-dependent manner after 24hr exposure. The 16S rRNA sequence-data revealed that aloin decreases the abundance of butyrate-producing bacterial species. Transepithelial resistant result revealed that aloin alters the intestinal barrier-function at higher concentrations (500 µM). In conclusion, aloin exhibits antibacterial property for certain commensal bacteria and decreases butyrate-production.